EXPERIM13NTAL CULTURE OF CHANOS IN FISH PENS IN A COASTAL LAGOON AT MANDAPAM - Lalmohan, R S (Indian Journal of Fisheries, 2011)
Chanos was experimentally cultured in three fish pens, fabricated with palmyrapoles and enclosed with 20-mm-mesh nylon webbing, of area 2500 m each.The methods of construction of the pens,, the hydrological conditions and generaltopography of the lagoon are described.